Italian Horror Cinema - Baschiera, Stefano 1977-; Hunter, Russ (Edinburgh University Press, 2022)
The first book-length academic investigation of Italian horror cinema, from the silent era to the presentIn its heyday from the late 1950s until the early 1980s Italian horror cinema was characterised by an excess of gore, violence and often incoherent plot-lines. Films about zombies, cannibals and psychopathic killers ensured there was no shortage of controversy, and the genre presents a seemingly unpromising nexus of films for sustained critical analysis. But Italian horror cinema with all its variations, subgenres and filoni remains one of the most recognisable and iconic genre productions in Europe, achieving cult status worldwide. One of the manifestations of a rich production landscape in Italian popular cinema after the Second World War, Italian horror was also characterised by its imitation of foreign models and the transnational dimension of its production agreements, as well as by its international locations and stars.This collection brings together for the first time a range of contributions aimed at a new understanding of the genre, investigating the different phases in its history, the peculiarities of the production system, the work of its most representative directors (Mario Bava and Dario Argento) and the wider role it has played within popular culture.ContributorsRuss Hunter (Northumbria University)Francesco Di Chiara (Università degli Studi di Ferrara)Stefano Baschiera (Queen's Universty Belfast)Johnny Walker (Northumbria University)Peter Hutchings (Northumbria University)Marcia Landy (University of Pittsburgh)Karl Schoonover (University of Warwick)Adam Lowenstein (University of Pittsburgh)Austin Fisher (Bournemouth University)Leon Hunt (Brunel University)Craig Hatch (University of Southampton)Mark Bernard (University of North Carolina)Paolo Noto (Università di Bologna)